SECONDARY CATARACTS AFTER IN-THE-BAG INTRAOCULAR LENS IMPLANTATION: RISK FACTORS AND WAYS OF PREVENTION (PART 3) - S. G. Toropygin; E. V. Glushkova (Российский офтальмологический журнал, 2018)
The third part of the paper (the first part see in ROJ, 2017; 10 (4): 105-12; the second - in ROJ, 2018; 11 (1): 103-10) reviews methods of eradication of lens epithelial cells and matrix for their proliferation, as well as the role of postoperative inflammation in posterior capsule opacification. For citation: Toropygin S.G., Glushkova E.V. Secondary cataracts after in-the-bag intraocular lens implantation: risk factors and ways of prevention (Part 3). Russian ophthalmological journal. 2018; 11 (2): 103-12. doi: 10.21516/2072-0076-2018-11-2-103-112 (In Russian).